Oesophageal high-resolution manometry: moving from research into clinical practice. Issue 3 (25th September 2007) - Fox, M R; Bredenoord, A J
Abstract : Manometry measures pressure within the oesophageal lumen and sphincters, and provides an assessment of the neuromuscular activity that dictates function in health and disease. It is performed to investigate the cause of functional dysphagia, unexplained "non-cardiac" chest pain, and in the pre-operative work-up of patients referred for anti-reflux surgery. Manometric techniques have improved in a step-wise fashion from a single pressure channel to the development of high-resolution manometry (HRM) with up to 36 pressure sensors. At the same time, advances in computer processing allow pressure data to be presented in real time as a compact, visually intuitive "spatiotemporal plot" of oesophageal pressure activity. HRM recordings reveal the complex functional anatomy of the oesophagus and its sphincters. Spatiotemporal plots provide objective measurements of the forces that move food and fluid from the pharynx to the stomach and determine the risk of reflux events. The introduction of commercially available HRM has been followed by rapid uptake of the technique. This review examines the current evidence that supports the move of HRM from the research setting into clinical practice. It is assessed whether a detailed description of pressure activity identifies clinically relevant oesophageal dysfunction that is missed by conventional investigation, increasing diagnostic yield and accuracy. The need for a new classification system for oesophageal motor activity based on HRM recordings is discussed. Looking ahead the potential of this technology to guide more effective medical and surgical treatment of oesophageal disease is considered because, ultimately, it is this that will define the success of HRM in clinical practice.